Bottom-up organic integrated circuits - Smits, Edsger C. P.; Mathijssen, Simon G. J.; Hal, Paul A. van; Setayesh, Sepas; Geuns, Thomas C. T.; Mutsaers, Kees A. H. A.; Cantatore, Eugenio; Wondergem, Harry J.; Werzer, Oliver; Resel, Roland; Kemerink, Martijn; Kirchmeyer, Stephan; et al. (Nature, 2008)
An ambition in the field of organic electronics has been to harness the self-organizing properties of certain classes of molecules to assemble key device structures without human intervention. Single, self-assembled layers of such molecules have been successfully implemented in transistors, but the devices' properties have not been promising, largely due to defects in the monolayers and poor electronic coupling between the molecules within the layers. It is now shown how such limitations can be overcome, by carefully tuning the properties of the molecules through chemical design to ensure dense, highly ordered packing in the self-assembled monolayer. The good electrical performance and high reproducibility of the resulting devices is demonstrated by combining over 300 of them into a functional integrted circuit.